Green Road Vegetation CO2 Sequestration Potential on Transportation Co2 Emissions - Salamah, Shalzafatihah; Hendriyanto Cahyonugroho, Okik (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2023)
Transportation is one of the anthropogenic activities that emit CO2. Its existence is essential for human mobilization, which causes the need for mitigation and solutions that can support the continuity of activities while minimizing the impact of emissions. In this case, the green belt of Jalan Jagir Wonokromo contains a mixture of road protection and CO2-absorbing vegetation that can reduce emissions. For this reason, a study was conducted to determine the CO2 absorption potential of green belt vegetation to provide information and a reference for optimizing green open space. The research was conducted using a quantitative descriptive method, which included measuring road ambient CO2 concentrations, calculating vehicle volume, measuring breast height diameter as a biomass component, and researching correcting CO2 absorption by vegetation. According to the research results, the average ambient concentration of CO2 on roads is 785 mg/m3. The transport CO2 concentration was calculated using a Tier II approach and yielded a value of 186.87 kg/hour, contributing 79% to the ambient CO2 concentration.Furthermore, a box model is used to analyze the concentration of CO2 that will be absorbed by vegetation, resulting in 103.47 tons per year. Meanwhile, the ability to absorb CO2 from vegetation is 152.74 tons/year after being corrected by a pilot-scale study that considers vegetation's age and physiological factors. All emissions on Jalan Jagir Wonokromo can still be absorbed by vegetation, but optimization needs to be done in the form of intensification, extensification, and mitigation.